Вы находитесь на странице: 1из 52

# . ..

.. , ..

" "

, 2009
22.161
65

-

( 2 22.10.2009 .)

:
.. . .-. ., , . -
.
..
.. ..-. ., ,
. .. -

65 .., .. -
: . :
, 2009 52 . .
-
,
,
, .
, , -
, .

c .., .. 2009

3

1 8

2 9

3
10

4 -
11

5 -
12

6 19

7 22

8
24

9 ,
26

10 34

11 43

51

-
, -
.
-
.
, -
, ( , -
), .
.
.

,
, -
.
: , -
, ,
, -
( ).
( , -
),
. -
(, ,
1886). , -
, .
, -
, ,
(, , , ),
. -
, , .
1.

Z
F (x) = ext cos tdt (0.1)
0

x, cos t
t :
Z
t2 t4 1 1 1
F (x) = ext 1 + dt = 3 + 5 .
2! 4! x x x
0

x > 1,
x
F (x) = .
x2 + 1
, , ,
(0.1) ; x > 1

5
x > 0.
2.

Z
ext
G(x) = dt. (0.2)
1+t
0

Z
1 1! 2!
G(x) = ext 1 t + t2 dt = 2 + 3 . (0.3)
x x x
0

x,

un+1 n

un = x (n )

(0.3), , .
: (1 + t)1 t 1. -
, , (0.3)
x, , x = 10.

## 0.1000 0.0100 + 0.0020 0.0006

0.0914. , -
G(10) = 0.09156 . . . . -
,
n (x) G(x) n- (0.3)

## n (x) = G(x) gn (x),

1 1! 2! n1 (n 1)!
gn (x) = + 3 ... + (1) .
x x2 x xn

n
1 n1 n1 (1) tn
= 1 t + t2 ... + (1) t + ,
t+1 1+t

6
(0.2)
Z
n tn ext
n (x) = (1) dt .
1+t
0

R n!
, |n (x)| tn ext dt =
n+1
,
0 x
(0.3) G(x) ,
. n
, x . (n = 4, x = 10)
4 (10) 0.00024.
, (0.3) : -
, {gn (x)}
G(x). -
. , , . -,
n (x) . -, -
, , -
,
. (0.3) : x -
s
(1) s!
,
xs+1
s [x], x.
. gn (x)
G(x), n [x], -
, , .
3. (0.3)

Z t
e
E(x) = dt (x > 0). (0.4)
t
x

n + 1 ,
n
ex 1! 2! 3! (1) n!
E(x) = 1 + 2 3 + + +
x x x x xn
Z
n+1 et
+(1) (n + 1)! dt .
tn+2
x

7
, , (0.3), . :
1 x
|n (x)| 6 (n + 1)! e .
xn+2
,
E(x) ( n), x.
x
lim n+1 (x) = .
x

1
x
f (x) g(x), -
, .
x R, g(x) x ,
.
f (x)
1.1. 1 x ,
g(x)
f g (x ) , f
g g f .
.
2 1 x
(x + 1) x2 (x ); sh x e (x +).
2
f (x)
1.2. 0 x ,
g(x)
f = o(g) (x ) , f ,
g.
.

1 1 1
=o (x ); = o(1) (x ).
x2 x x

f (x)
1.3. ,
g(x)
f = O(g) , f , -
g.

8
, , c R , x > x0
|f (x)| 6 c|g(x)| (x > x0 ).

## sin x = O(1) (x R); sin x = O(x) (x R).

1.1. O

, [a, ). ,

(x)
f = O(g) x [a, ) , fg(x) -
[a, ). , o

.

1.2. x
, c. ,
c 6= 0, x c

(x2 c2 ) 2(x c)
2
= O(x c) = o(1).
x c
c -
.

1.3. x ,

. ,
1 1
sin n + =O (n , n ).
n n

.
1
x2 = O(x) (x 0); x = O(x2 ) (x ); ln x x = O(1) (x );

1
= O(x) (x ); ex = 1 + x + O(x2 ) (x 0).
sin x1

2
O o

f ,

9
(1.2) (1.3). , o(x) (x ) -
f (x)
f (x), : 0 (x ).
g(x)
O(g). ,

## o(g) + o(g) = o(g), o(g) = O(g).

, , -
, : O(g) = o(g) . ,
o(x) O(g).
.
.

## O() + O() = O(|| + ||); O(O()) = O();

O(o()) = o(O()) = o(o()) = o(); O()o() = o()o().

3

P

. as z s |z| < r. -
s=0
n

X
Rn1 (z) := as z s = O(z n )
s=n

|z| 6 , < r.
s
. 0 (, r). as 0 0 s .
s
, A, |as |0 6 A (s = 0, 1, 2, ...).
s
X X X

s s 0s z
|Rn1 (z)| = a z 6 |as ||z| = |as | 0 6
s=n s
s=n s=n
n n (1n)
z 1 |z| A0
6 A 0 = A0 (1n) 6
n
|z| .
z 0 |z| 0
1 0

10
P

xk
. 1. ex = 1 + x + k! = 1 + x + O(x2 ) (x 0)
k=2
2. ln {1 + O(x)} = O(x) (x 0).

4
-

,
, , -
, . -
, , f (x) , f (x) x
x ; a . x
Z
x+1
f (t) dt ( < 1), (4.1)
+1
x

Zx
c, < 1
f (t) dt ln x, = 1 , (4.2)

x+1
+1 , > 1
a
c .
, , (4.2).
f (x) = x {1 + (x)}, |(x)| < , x > x0 > 0.
x > x0
Zx Zx0 Zx
1 +1
f (t) dt = f (t) dt + x x0 +1 + t (t) dt ,
+1
a a x0

Zx Zx0 Zx
+1 +1 x0 +1 +1
f (t) dt 1 = +1 f (t) dt +1 + +1 t (t) dt .
x+1 x x x
a a x0

x , .
.

11
. 1, 2 (4.2).

. , f (x) = x + cos x,
f (x) x x , f 0 (x) 1 . , -
,
. -
.
. f (x)
f (x) xp x , p > 1. , f 0 (x) -
x, f 0 (x) pxp1 .
. f (x) = xp {1 + (x)}, |(x)| 6
R
x+h
x > x0 . h > 0, hf 0 (x) 6 f 0 (t) dt = f (x + h) f (x) =
x
R
x+h
p1 p
= p tp1 dt + (x + h)p (x + h) xp (x) 6 h p(x + h) + 2(x + h) .
x
1
h = 2 x.
n
p1 o x0
f 0 (x) 6 pxp1 (1 + ) + 2p1 x> .
1
,
n
0 p1
p1 o x0
f (x) > px (1 ) 2p1 x> .
1
. u x [1; ); ,
Z 2
dt 1 1 u
1 = +O 2 +O 3 .
t(t2 + t + u) 2 x x x
x

5 -

1. x + th x = u.

f (x) = x + th x = u, (5.1)

12
u .
1
f 0 (x) = 1 + 2 > 0,
ch x
f (x) , (5.1)
u R (. . 1).

. 1:
x(u) -
u? x , (5.1)
. th x -
"":
x = u th x.
| th x| < 1, ,
x(u) u (u ).

13
x(u).
, -
. th x = 1 + o(1) (x ),

## x(u) = u 1 + o(1) (x +). (5.2)

, th x
, x:
sh x ex ex 1 e2x
thx = = x x
= =
ch x e +e 1 + e2x

= (1 e2x ) 1 e2x + e4x e6x + O e8x =

= 1 2e2x + 2e4x 2e6x + O e8x (x > 0),

x u. (5.2) ,

e2x = O(e2u ).

-

x = u 1 + O e2x = u 1 + O e2u .

x = u 1 + 2exp 2u + 2 + O e2u + O e4u =
(5.3)
= u 1 + 2e2u+2 + O(e4u ).

, .
-
,
, , -
u = 5 O(e4u ) (5.3). ,
x = 4.0006709..., , , -
, 4.0006698.
2. , ,
xtg x = 1.
:
1
x = n + arctg ,
x

14
. 2:

n ,
.
2 ; 2 , ,
x n n . , x > 1,
1 1 1 1 1
arctg = 3 + 5 7 + ... .
x x 3x 5x 7x
,

1 1
x = n + O = n + O .
x n

,

1 1 1 4 1
x = n + +O x = n + +O ..
n n3 n 3(n)3 n5
3.

f (x) := x2 ln x = u, (5.4)

u . -
, "" ln x -
x 0. ,

15
. 3:

## (5.4) : x1 (u) +, x2 (u) +0 u +.

, -
.

5.1. ( -
).
g() ,
a < < g() ( ). (u) -
g() = u, (a, ), u > g(a).
(u) u (u ).

. , (a, ) -
g() = u (u), -
u .
g() , g() = u

[1 + o(1)] = u

16
. 4:

, u .
u
(u) = = u[1 + o(1)] (u ).
1 + o(1)

x2 ln x = u.
) x
ln x
, .. 2 0 (x ).
x

ln x
f (x) := x ln x = x 1 2 x2 (x ).
2 2
x
x2 = :
1 1 1
f ( 2 ) = ln = u = u + ln .
2 2
. (5.1) :
(u) = u[1 + o(1)] (u +).

17
, :

1 1
= u + ln = u + ln {u[1 + o(1)]} =
2 2
1 1 1
= u + ln u + ln [1 + o(1)] = u + ln u + o(1) (u +).
2 2 2

1 1
= u + ln u + ln u + o(1) =
2 2

1 ln u 1
= u + ln u 1 + +o =
2 2u u

1 1 ln u 1
= u + ln u + ln 1 + +o =
2 2 2u u

1 ln u 1
= u + ln u + +o (u +).
2 4u u
. 2 , -
.
) x 0.
f (x) = x2 ln x .
t = ln x, .. x = et ,
:
g(t) t + e2t = u t = u e2t . (5.5)

,
g(t) t (t +).
. , -
(5.5).
. ,
xtg x = u,
0; , :
2

1 2
3 3
x= 1u +u u + O u4 .
2 2 24

18
. , -
tg x = x
2
x = 1 3 + O 5 ( ),
3

= n + 12 , n .

6
P

f (x) x R, an xn
n=0
x ( -
), Rn (x) f (x) n-
Sn1 (x). ,
a1 a2 a3 an1
f (x) = a0 + + 2 + 3 + + n1 + Rn (x). (6.1)
x x x x
6.1. (, 1886). ,
P
an xn f (x) -
n=0

a1 a2 a3 an
f (x) a0 + + 2 + 3 + + n + (x ), (6.2)
x x x x

## n N Rn (x) = O(xn ) (x ). (6.3)

6.1. (6.3)
n 6 N , , (6.2) -
N - .
6.2. (6.2) .
, (6.2)
, .
(
P

x x1 ) , an xn
n=0
x, -
. , ,

19
, .
.

f (x)
(6.2)?

6.1. , f (x) -
(6.2) ,

( n1
)
X ak
lim f (x) = a0 , lim xn f (x) = an , n = 1, 2, . . . . (6.4)
x x xk
k=0

.
. (6.4),
n1
X ak an
Rn (x) = f (x) k
= n [1 + o(1)] (x ),
x x
k=0

Rn (x) = O(xn ) (x ).
.
(6.2). Rn (x) = O(xn ) :
n o
n n an n 1
x Rn (x) = x + Rn+1 (x) = an +x Rn+1 (x) = an +O (x ).
xn x

(6.4).

6.2. ( ).
f (x) (a, ) R
(6.2).

, (6.4)
( ) .

6.3. , , : -
,
.

20
.
f (x) = ex
a0 = lim f (x) = 0, a1 = lim xex = 0
x x

..; ,
0 0 0
ex 0 + + 2 + + n + ... (x ).
x x x
,
a1 a2 an
g(x) a0 + + 2 + + n + (x ),
x x x
a1 a2 an
g(x) + kex a0 + + 2 + + n + k R.
x x x
1 1 + ex 1
. , , ,
1 + x 1 + x 1 + e x + x
x ,

X k
(1) x(k+1) .
k=0

, -
,
.
, f (x)
f (x)
(6.2), , (x) ,
(x)
.

X ak
f (x) (x) .
xk
k=0

, f (x) (x) -
(6.2),

X ak
f (x) (x) + .
xk
k=0
1
. , x 2 , sin x, ln x
(6.2).

21
7 -

1. -
P
P

. f (x) fk xk , g(x) gk xk , , R
k=0 k=0

X
f (x) + g(x) (fk + gk )xk .
k=0

2. :

X
f (x)g(x) hk xk (x +),
k=0

hk = f0 gk + f1 gk1 + ... + fk g0 .
,
P
n1 P
n1
f (x) = fk xk + Fn (x), g(x) = gm xm + Gm (x),
k=0 m=0
Fn (x) = O(xn ), Gn (x) = O(xn ) (x +)
P
n1
f (x)g(x) hk xk = Hn (x),
k=0

n1
X fk
Hn (x) = Gnk (x) g(x)Fn (x) = O(xn ) x .
xk
k=0

3. .
f0 6= 0 x (, |F1 (x)| < |f0 |).
1 1 1 1
= = =
f (x) f0 + F1 (x) f0 1 + F1 (x)
f0
k k n
P
1 n1 k F1 (x) (1) (F1 (x))
= (1) + n =
f0 k=0 f0 f0 [f0 + F1 (x)]
k
P (1)k f1
n1 f2 fn1
k
(1) {F1 (x)}
n
= k+1
+ + + + F n (x) + .
k=0 f0 x x2 xn1 f0 [f0 + F1 (x)]
1 1
F1 (x) = O Fn (x) = O n ,
x x

22
n1
X hk
1 1
= + O (x ),
f (z) xk xn
k=0
hk -

## f0 hk = (f1 hk1 + f2 hk2 + + fk h0 ), k = 1, 2, . . . ,

1
f (x) = 1.
f (x)
. ( -
) f0 = 0.
4. .

f1 f2 fn
f (x) f0 + + 2 + + n + (x ),
x x x
f (x) .
f0 = f1 = 0, f (t)
x < t < , .
-
f1 1
, f (t) f0 O 2 t
t t
.
4, ,
Z
f1 f2 f3 f4
f (t) f0 + 2 + 3 + (x ).
t x 2x 3x
x

5.
. , f (x) = ex sin ex ,
0 0
f (x) 0 + + 2 + (x ).
x x
f 0 (x) = cos ex ex sin ex x -
. , -
, f 0 (x)
. ,
f 0 (x) ( 4)
.

23
8 -

1. . -
.
, x
1
c, (x c). -
x
, n N

## f (x) = a0 + a1 (x c) + a2 (x c)2 + a3 (x c)3 + +

n1
+ an1 (x c) + Rn (x)

n
Rn (x) = O((x c) ) (x c),

X k
f (x) ak (x c) (x c).
k=0

c -
. ,

c = .
2. , .

{n (x)}n=0 -
c.

8.1. {n (x)}n=0
( ), n N

## n+1 (x) = o(n (x)) (x c).

8.2. , f (x)
P
{n (x)} f (x) an n (x),
n=0

n1
X
n N f (x) = ak k (x) + Rn (x), Rn (x) = O(n (x)) (x c). (8.1)
k=0

24

(8.1). -
, n (x)m (x)
,
.
a) .
1
, , f (x) = .
k1 1 + x
) x k=0
(x +).
X
1 1 1 1 1 1 k
= 1 = 1 + 2 (1) xk1 .
1+x x 1+ x
x x x
k=0

) (1 x)x2k2 k=0 (x +).
1 1x 1 1
= = (1 x) 2 =
1+x 1 x2 x 1 x12
X
1x 1 1
= 2 1 + 2 + 4 + (1 x)x2k2 .
x x x
k=0

) (1 x + x2 )x3k3 k=0 (x +).

1 1 x + x2 1 x + x2 1
= = =
1+x 1 + x3 x3 1 + x13

1 x + x2 X k 3k
X k1x+x
2
= (1) x (1) .
x3 x3k+3
k=0 k=0

4. ?

. , ,

X ak
f (x) ; xk , x +. (8.2)
xk k=0
k=0

, :

X a2k a2k+1
f (x) + . (8.3)
x2k x2k+1
k=0

25
, (8.3) , (8.2),

a2k a2k+1
k (x) = 2k + 2k+1
x x
, (8.2): k (x) = o(xk )
x +.
, , -
, , -
. ,

sin x X k! exp k+1 2k x
k
.
x (ln x)
k=1

. {n (x)}
, x c R. ,
Rx
n (t)dt x c f (x)
c
P

, f (x) ak n (x)
k=0
(x c),
Zx
X Zx
f (t)dt ak k (t)dt (x c).
c k=0 c

9 -
,
1. -
, , -
. ,
,
. , .

9.1. -
R ext
G(x) = dt x + "-
0 1+t
1 P
k
" , (1) tk ,
1+t k=0

26
|t| < 1. -
. ,
:
Z xt
ext e dt = dv, v = 1 ext
G(x) = dt = 1 = u, du = 1x dt =
1+t 1+t (1+t)2
0
t= Z Z xt
1 ext 1 xt dt 1 1 e dt
= e 2 = =
x (1 + t) t=0 x (1 + t) x x (1 + t)2
0 0
1
= + R2 (x).
x
:
Z t=
1 xt 1 ext 1
|R2 (x)| e dt = = 2.
x x (x) t=0 x
0

(9.1) ,
(!):
Z
1 1 ext
G(x) = 2 dt =
x x (1 + t)
0
xt
e dt = dv, v = 1 ext
= 1 = u, du = x2 dt =
(1+t)2 (1+t)3
Z
1 1 1 ext 1 xt 2
= e dt =
x x x (1 + t)2 x 3
(1 + t)
0 0
Z (9.1)
1 1 2 ext
= 2+ 2 3 dt =
x x x (1 + t)
xt
e dt = dv, v = x1 ext
= 1 = u, du = 3 dt =

(1+t)3 (1+t)4
Z
1 1 2 1 ext 3ext
= 2+ 2 3 4 dt =
x x x x (1 + t) x(1 + t) 0 0

27

Z xt Z xt
1 1! 2 1 3 e 1 1! 2! 3! e
= 2+ 2 4 = 2+ 3 3 4 dt.
x x x x x (1 + t) x x x x (1 + t)
0 0

(9.1) ( ),
n :
Z
dt
G(x) = ext =
1+t
0
(9.2)
n
X k n+1 Z
(1) k! (1) (n + 1)! ext
= + dt.
xk+1 xn+1 (1 + t)n+1
k=0 0

(9.2) :
Z Z
(n + 1)! ext dt (n + 1)!
|Rn+1 (x)| = n+1 n+1 xn+1 ext dt =
x (1 + t)
0 0 (9.3)

(n + 1)! 1
= = O n+2 .
xn+2 x

, (9.2)(9.3) -
:
Z
ext dt X (1) k!
k
G(x) = .
1+t xk+1
0 k=0

. ,
Z
et dt
F (x) = (x +0)
1 + xt
0

Z
X
et dt n
(1) n!xn (x +0).
1 + xt n=0
0

28
. -
-
,

Zx Z
2 t2 2 2
erf x = e dt, erfc x = et dt.

0 x

2
, -

erf x + erfc x = 1.
:

exp (x2 ) X n (2n 1)!!
erfc x (1) n , (x +). (9.4)
x n=0 (2x2 )

, (9.4) -

.
. (9.4) t2 = u -
.
. ,
Z
(n + 1, x) = et tn dt,
x

-
Z Zx
(n + 1, x) = (n + 1) (n + 1, x) := et tn dt et tn dt,
0 0

X (n + 1)
(n + 1, x) ex xn xk (x ) (n
/ Z).
(n + 1 k)
k=0

29
9.2. .

Z Z
2
cos t dt sin t2 dt,
x x

(
)

Z Z
cos u sin u
du du.
u u
0 0

ei = cos + isin

Z iu
1 e
F x; := 1 du , (9.5)
2 u2
x2

x 6= 0.

(9.5) :

Z it
it Z it
eit e dt = dv, v = 1 eit 1 e e
dt = 1 i
1 dt =

1/2
+ dt =
t1/2 t 1/2 = u, du = 2t 3/2 i t t=x 2 2it 3/2
x2 x2
2 Z 2
eix i eit eix i 3
=i 1+1/2
dt = i F x; .
x 2 t x 2 2
x2

( !)

1
F x; =
2
n (9.6)
ieix X 12 + k
2
1 12 + n + 1 1
= + n+1 F x; + n + 1 .
x 12 (ix2 )k
k=0
i 12 2

30
(9.6)
Z

12 + n + 1 eit
|Rn+1 (x)| = 1 n+1+1/2
dt 6 eit = 1 6
2 2 t
x
Z
21 + n + 1 dt n + 32 2 1 (2n+1)
6 1 = = O x
2 tn+3/2 12 (2n + 1) x2n+1
x2
x .

, F x; 12
2 n
1 ieix X 12 + k 1
F x; 1 k
(x ). (9.7)
2 x 2 (ix2 )
k=0

-
(!)
Z
cos t2 dt
x
( m )
1 X 2m + 23 (1) X 2p + 12 1
2 2
cos x sin x ,
2x m=0
12 x4m+2 p=0
12 x4p

Z
sin t2 dt
x
( m
)
1 X 2p + 12 (1)p 1 X 2m + 32 (1)
2 2
cos x + sin x
2x p=0
21 x4p m=0
12 x4m+2

(x ).

. ,

1
Z eit
F x ;a =
2 dt (a > 0)
ta
x

31
(. (9.7))
Z
eit ieix X (k + a) 1
a
dt a (x ).
t x (a) (ix)k
x k=0

2. . , -
, :
Z
J(x) = ext q(t)dt,
0

J(x)
[0; ) ,

## q (n) (t) = O(et ), R, 0 6 t < , n = 0, 1, 2, . . . .

, J(x) x > . ,

Z Z

|J(x)| = e q(t)dt 6 ext |q(t)|dt 6
xt

0 0
Z Z
C
6 ext Cet dt = C e(x)t dt = (x > ).
x
0 0

:
Z
q(0) q 0 (0) q (n1) (0) 1
J(x) = + 2 + + n
+ n ext q (n) (t)dt.
x x x x
0

1 R
Rn+1 (x) := ext q (n) (t)dt:
xn 0
Z Z
1 1
|Rn+1 (x)| 6 ext |q (n) (t)|dt 6 ext Cn et dt =
xn xn
0 0

Cn 1 1
= = O n+1 (x +).
xn x x

32

X q (k) (0)
J(x) (x +). (9.8)
xk+1
k=0

t2 00 tn
q(t) = q(0) + tq 0 (0) + q (0) + + q (n) (0) + .
2! n!
,
Z
X Z
xt 1 (k)
e q(t)dt q (0) tk ext dt = (xt = ) =
k!
0 k=0 0

X Z
q (k) (0) 1
= k e d .
k! xk+1
k=0 0

R
k e d = (k + 1) = k!, -
0
(9.8).
(9.8) -
x1 .
,
q(t) t = 0
t?
.

. (, 1918).

X
q(t) ak t(k+)/ (t 0),
k=0

, > 0.
Z
X
xt k+ ak
e q(t)dt (x +)
k=0
x(k+)/
0

33
, -
x.
( ).

. ,
Z 12
X 2 2 2 2
k 1 3 5 ...(2k 1)
exch t q(t)dt ex (1) k
.
2x k!(8x)
0 k=0

ch t = + 1 0 <

. ,
Z
X 2
k [(2k 1)!!]
exsh t q(t)dt (1) .
x2k+1
0 k=0

10
1. . -

Zb
I(x) = exp(t) q(t)dt (x +), (10.1)
a

a, b, p(t), q(t) x. -
(1820).
() exp(t)
t = t0 , p(t) . x ,
, (
2
ext t = 0) , -
t0 .
p(t) q(t)

34
(t t0 ), , -
,
+.
.
2. .
) , , t0 = a, p0 (a) > 0 q(a) 6= 0.
:
Zb
0
I(x) ex[p(a)+(ta)p (a)] q(a)dt
a
Z (10.2)
xp(a) 0 q(a)exp(a)
q(a)e exp (a)(ta) d(t a) =
xp0 (a)
a
(x +).
) C , p(t)
t0 (a, b) q(t0 ) 6= 0.
Zb
1 2 00
I(x) exp x p(t0 ) + (t t0 ) p (t0 ) q(t0 )dt
2
a
Z
1
q(t0 )exp(t0 ) exp xp00 (t0 )(t t0 )2 dt.
2
00

r p (t0 ) > 0,
xp00 (t0 )
= (t t0 ). ,
2
R 2
e d = , :

12
xp(t0 ) 2
I(x) q(t0 )e (x +). (10.3)
xp00 (t0 )
10.1. (10.2) (10.3)
, -
, : -, p(t) q(t)
(tt0 ), , -,
"b" (10.2) (10.3) "a" (10.3).

35
..1,2 -
. , , -
, -
I(x) (10.2) (10.3).
3. ( ).
, "a" ; -
, p(t) t = a;

p(t) , , -
t. "b" , p(t) ,
q(t) . ,
:
1) p(t) > p(a) t (a, b) c (a, b)

## inf [p(t) p(a)] > 0,

t[c,b)

p(t) t = a.
2) p0 (t) q(t) t = a, , -
, t = a.
1
3) t a + 0 p(t) p(a) P (t a) , q(t) Q(t a) ,
.
P, , , Q 6= 0
.
4)
Zb
I(x) := exp(t) q(t)dt
a

-
x.

. (). 1)-4),
xp(a)
Q e
I(x) (x +). (10.4)
(P x)

10.2. , ,
(10.4) (10.2) (10.3).

36
, ) .2, p(t)
t0 = a, p0 (a) > 0 q(a) 6= 0, 1):

= 1, P = p0 (a), = 1, Q = q(a).

(10.4) (1) = 1,
(10.2).

), p(t) -
t0 ,

1 00
= 2, P = p (a), = 1, Q = q(t0 ).
2

(10.4), 12 = ,
, (10.3)
( ?).

. 1. 2) 3) ,
"c "a (a, c] p0 (t)
, q(t) . p(t) -
(a, c],

= p(t) p(a).

(t) t( )

Zc Zd
xp(a) xp(t)
e e q(t)dt = ex f ( )d , (10.5)
a 0

dt q(t)
d = p(c) p(a), f ( ) = q(t) = 0 .
d p (t) t=t( )
, d , f ( )
t (0, d).
2. 3) t a + 0

= p(t) p(a) P (t a) ,

37
,
1
ta ( +0).
P

(1)
q(t) Q P
Q 1
f ( ) = 0 (1) = ( +0). (10.6)
p (t) P
P P

3. (10.6), (10.5) :

Zd
ex f ( )d =
0
Zd Zd "
#
x Q 1 x Q 1
= e
d + e f ( ) d =
P P
0 0

Z Z
Q
= ex 1 d ex 1 d + (10.7)
P
0 d
Zd "
#
Q 1
+ ex f ( ) d =
P
0

Z
Q
= ex 1 d 1 (x) + 2 (x).
P
0

(10.7) (10.4).
, x = ,
(!):
Z Z
Q x
1
Q
1
Q
e d = e d = . (10.8)
P (P x) (P x)
0 0

## (10.5), (10.7) (10.4).

4. , (10.7)

38
, .
) > 0. d ,

Q 1

|Q| 1

f ( ) < (0 < 6 d). (10.9)
P

P

, "c"
"a" (10.6).
) (10.9), - (10.8)
:

d " #
Z
1
Q
|2 (x)| = ex f ( ) d 6
P
0
Zd Z
x |Q|
1
|Q| x
1
|Q| 1
6 e d 6 e d = .
P P (P x)
0 0

) 1 (x) -

Z
(; x) = et t1 dt,
x

Z
x =
1 (x) = ex 1 d = =
d = x1 d
d
(10.10)
Z

1
1 1
= e d = ; xd .
x x
xd

39
. ,

(; x) = ex x1 + ( 1)( 1; x) = =

x 1 1 ( 1)( 2) . . . ( n + 1)
=e x 1+ + + +
x xn1
Z
+ ( 1)( 2) . . . ( n) et tn1 dt
x

X ( 1)( 2) . . . ( k)
ex x1 (x ).
xk
k=0
(10.11)

(10.11), (10.10):
xd
1 e
1 (x) = ; xd = O (x ). (10.12)
x x

) , x0 x,
I(x) .

[c,b)

## xp(t) xp(a) = (x x0 ){p(t) p(a)} + x0 {p(t) p(a)} >

> (x x0 ) + x0 p(t) x0 p(a).

, :

Rb
xp(a) Rb xp(t)
e e q(t)dt 6 e[(xx0 )+x0 p(t)x0 p(a)] |q(t)|dt =
c c
(10.13)
Rb
= e(xx0 )+x0 p(a) ex0 p(t) |q(t)|dt = O(ex ) (x +).
c

40
) (5) (7), :

Rc Rb
I(x) = exp(t) q(t)dt + exp(t) q(t)dt =
a c
Rd Rb
= exp(a) ex f ( )d + exp(t) q(t)dt =
(
0 c )
xp(a)
R
d
x xp(a)
Rb xp(t)
=e e f ( )d + e e q(t)dt =
c
(0 )
Q
R
1
Rb
= exp(a) ex d 1 (x) + 2 (x) + exp(a) exp(t) q(t)dt .
P
0 c
(10.14)
(10.4), (10.14),
, (10.12) (10.13) x

x . , x,
d
1 xd
ex = o(x ), e = o(x ) (x +).
x
-
I(x).
I(x). -
.

. ( I(x)).
1), 2) 4) , 3) -
:

X k+
p(t) p(a) + pk (t a) ,
k=0

X k+1
q(t) qk (t a) t a + 0,
k=0

. ,
,

X k+1
p0 (t) (k + )pk (t a) (t a + 0).
k=0

41

Zb
X
k+ ak
exp(t) q(t)dt exp(a) (x +),
(k+)
x
a k=0

ak pk qk .
10.1.

Z
1
In (x) = excos t cos ntdt.

0

:
t2
p(t) = cos t = 1 + + O t4 t 0; a = 0, p(a) = 1;
2
1 1 1 1
q(t) = cos nt = + O t2 ; P = , = 2, Q = , = 1.
2
:
x(1)
1 1 e 1 ex ex
In (x) 1/2
= 1/2 = (x +).
2 2 1
x 2 x 2x
2 2

10.2.
Z1
1
I(x) = ex t
sin tdt.
12
0

1 1
p(t) = t1/2 , q(t) =
sin t t (t 0),
12 12
1 1
p(a) = 0, a = 0, P = 1, = , Q = , = 2.
2 12
:
1 e0 1
I(x) 2 (4) 4 = 4 , x +.
12 x x

42
, ak pk qk
( . [1], . 114), -
I(x).

.

R4
1. I(x) = ext tg2 t dt.
0

R 2
2. I(x) = ext sin t dt.
1

R1 sin 2t
3. I(x) = ext dt.
1 t

R2
ex(t 2t1)
2
4. I(x) = t2 + 2t dt.
0

11
1. . .

Zb Zb
cos [xp(t)]q(t)dt, sin [xp(t)]q(t)dt, (11.1)
a a

a, b, p(t) q(t) x.
x ? -
x ,
.

:
1) "a" "b" ( ) -
;
2) p0 (t), p(t)
" ".
.

43
2. . (11.1) -
,

Zb
I(x) = eixp(t) q(t) dt. (11.2)
a

) "a" -

a :

## exp {ix[p(a) + p0 (a)(t a)]}q(a)

, (11.3)
ixp0 (a)

, p0 (a) 6= 0. t = a I(x)

eixp(a) q(a)
.
ixp0 (a)

t a, (11.3) -
,
(11.3). ,
t = b

eixp(b) q(b)
.
ixp0 (b)

) t0 (a, b)
p(t), ..

1
2 3
p(t) = p(t0 ) + (t t0 ) p00 (t0 ) + O (t t0 ) , t t0 .
2
(11.2)
:
1
exp ix p(t0 ) + p00 (t0 )(t t0 )2 q(t0 )
2

44
, p00 (t0 ) q(t0 ) . -
, , t0 -
, +. -
(. ).
:
Z
1 00 2
exp ix p(t0 ) + p (t0 )(t t0 ) q(t0 )d(t t0 ) =
2

Z
1 00 2
= exp {ixp(t0 )}q(t0 ) exp ix p (t0 )(t t0 ) d(t t0 ) =
2

= x2 p00 (t0 )1/2 (t t0 ) = = (11.4)
Z
d
= exp {ixp(t0 )}q(t0 ) exp i sign [xp00 (t0 )] 2 =
x p00 (t0 )1/2
2
s Z
2 2
= eixp(t0 ) q(t0 ) ei d .
|xp00 (t 0 )|

,
Z Z 2 Z
i 2 i 2
= y y > 0 dy
e d = 2 e
d = = 2 eiy =
2 d = dy 2 y
0 0

Z
1
= eiy y 2 1 dy.
0

Z
ei/2 ()
eiy y 1 dy = .

0

## 11.1. 0 < < 1 , ..

6 0
> 1.

45
.
I
eiz z 1 dz
L

l, . 5.

. 5:

. ,

I ZR ZR
iz 1 iy 1 1
e z dz = e y dy + IR + ei(it) (it) d(it) + Ir ,
L r r

IR Ir .

ZR ZR
iy 1
e y dy = et t1 dt i IR Ir . (11.5)
r r

,
lim Ir = 0, lim IR = 0.
r0 R

46
,

Z0 Z2

Ir = exp irei r ei(1) iei d = ir er(icos sin )+i d.
0
2

Z2 Z2
r0
|Ir | 6 r ersin d 6 r d = r 0.
2
0 0

,

Z2 Z2

IR = i exp iRei R ei d = iR eR(icos sin )+i d
0 0

Z2
|IR | R eRsin d.
0
2
sin > ( 0 6 6 ), -
2
:
2
ersin 6 er

Z2
= 2
2

2 e R
R1
|IR | 6 R r
e
d = R R = 1 eR 0
2 =0 2
0

(R +),
< 1.
i
, i = e 2 , (11.5) ,
r 0 R +:
Z Z
iy 1 i i ()
e y dy = e 2 et t1 dt = e 2 .

0 0

47
,
eiz z 1 ,
L( . . 5) Oy (!).
. ,

Z
+
2 i 1 i
ei d = e 4 = e 4 .
2

, (11.4) :

Zb s
ixp(t) i ixp(t0 ) 2
I(x) = e q(t)dt e 4e q(t0 ) (x ). (11.6)
|xp00 (t0 )|
a

11.2. 1) ,
), (11.6), , (11.6) -
( x ), -
, p(t).
2) :
) .
) , q0 = 0.
3) I(x) x ,
(11.6) -
( ) (
a 6= ,b 6= +).
4)
. , -
, , -
.

3. . ,
) (11.6), -
. , ,
(11.2)
p(t) q(t).

48
, -
.

Zb
I(x) = eixp(t) q(t)dt
a

, :
1) a , p(t) , q(t) -
. [a, b] , p0 (t)
, t0 = a. x
p0 (t) ; , ,
i
.
2) (a, b) p0 (t) q(t) , p0 (t) > 0,
p00 (t) q 0 (t) ,
.
3) t a + 0
1
p(t) p(a) P (t a) , q(t) Q(t a) ,

, -
. P , , ,
Q .
Wb
4) { pq(t)
0 (t) } c (a, b).
c
, f [c, b] -
:

b
_ Zb
(f ) = |f 0 (x)|dx.
c c

q(t)
5) t b 0 ,
p0 (t)
, p(b) = .

. , 1) 5) ,

49
, < .
ixp(a)
i Q e
I(x) e 2 , x +.
(P x)/

1. ,

Z2
1 1
tsin (x cos t)dt = cos x + o (x ).
x 2 x
0

2. , x
Z
i ix
(1 e1t )eixt(1ln t) dt e .
x
1

3. , x +
Z r
1 1
texp it2 (ln t x) dt exp x ie2x1 + i .
e 2 4
0

50

[1] .
. .: , 1978. 376 c.
[2] . . . .: ,
1966. 248 c.
[3] . . . .: , 1966.
160 .
[4] . . . .: , 1977. 368 c.
[5] . . .
.: , 1979. 320 c.
[6] . . .: , 1962.
128 .
[7] . M. . :
.., 2007. 135 c.

51

:
,

: ..

30.10.2009. 7084/16.

. . 2,4 .. 100.